Interação de isolados de Trichoderma spp. e preparados homeopáticos : estudo in vitro e no desenvolvimento inicial do tomateiro-cereja - França, Danilo Vieira Cardozo (2016)
The fungi of genus Trichoderma are found inhabiting the rhizosphere of plants acting as biological control agents and plant growth promoters. The homeopathic preparations have the potential to assist the vegetative development, promoting adaptation to climate conditions and absorption of nutrients. The interaction between techniques that aim the sustainability of the production system is one of the principles of agroecological view. This study aimed to evaluate the interaction of Trichoderma spp. and homeopathic preparations in vitro and initial development of cherry tomato. The isolates of Trichoderma spp., obtained in the laboratory from soil samples, were subjected to in vitro assays for evaluating the production of indoleacetic acid and phosphate solubilization. The selected isolates were analyzed in relation to mycelial growth, sporulation and germination of spores under the influence of homeopathic treatments (Carbo vegetabilis 6CH and Phosphorus 6CH). In the experiment with cherry tomato, were compared the plant height, stem diameter, fresh and dry shoot, root, leaves and stems, also was determined the leaf area, chemical composition found in the shoot using homeopathic treatments Carbo vegetabilis 6CH and Phosphorus 6CH, such as Trichoderma “F”, “R” and Trichodermil®. The in vitro tests showed that two isolates produced indoleacetic acid and four isolates were higher in phosphate solubilization. It was also observed that Phosphorus increased the speed of mycelial growth of Trichoderma, and positively influenced the sporulation of the isolates. The Carbo vegetabilis treatment provided an increased number of germinated conidia of Trichoderma “F” isolated. In the experiment with cherry tomato it was found that the use of treatments did not influenced on plant height, but it was observed interaction between Trichderma and homeophatic preparations in the increase of diameter stem. It has been found that the use of Trichoderma promoted an increased leaf area index, fresh and dry weight of leaves. The homeopathic treatment Carbo vegetabilis 6CH provided gains on the plant roots. The homeopathic treatments and Trichoderma isolades had influence on cherry tomato above the use of soil nutrients.